THE REPRESENTATION OF THE IDEAL SUNDANESE, ACCORDING TO KANG DEDI MULYADI YOUTUBE CHANNEL - Yudhistira, Dimas; Fathonah, R.D. Nuraini Siti (International Journal of Humanity Studies (IJHS), 2023)
Celebrity, including politicians, is often seen as the epitome of one specific culture. Dedi Mulyadi attempts to present himself as an ideal Sundanese for his viewers through his YouTube channel. With almost 4 million subscribers, the politician has become an internet sensation as his Sundanese characteristics reach many viewers. This article tries to elaborate on the idea of being Sundanese according to Dedi Mulyadi's YouTube Channel. There are many ways to elaborate on this idea; this article focuses on his utterances in interacting with certain people. Thus, the pragmatic approach covering mixing code, speech act, and the representation issue is applied in this article to break down the selected conversation. Eventually, the findings show that Dedi Mulyadi uses conversational pragmatics to represent himself as an ideal Sundanese. According to his videos, the caring, compassionate, yet assertive leader is what it means to be an ideal Sundanese.